2021
DOI: 10.1002/jlb.4a1020-641rr
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of maturation and activation markers on NK cells in patients with active and latent tuberculosis

Abstract: NK cells were recently suggested to be important for the initial control of M. tuberculosis infection. The phenotypes of the 3 main NK blood subsets, CD56bright, CD56dim, and CD56neg cells, were characterized by flow cytometry in a cohort of 81 prospectively enrolled subjects (21 untreated patients with active tuberculosis ‐aTB‐, 35 latently TB infected ‐LTBI‐ subjects, and 25 non‐infected controls), using 9 different mAbs added to whole blood. Compared to LTBI subjects, patients with aTB had lower proportions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…The amount of NK cells was also found to be remarkedly decreased after 7 day-stimulation with MTB antigens. 42 Our results also showed that MTB lysates impaired the proliferative capacity of NK cells, most likely due to virulence factors released after the destruction of bacterial cells. 52 This effect is reminiscent of a previous study demonstrating that cytomegalovirus infection has the potential to shape the NK cell repertoire, thus resulting in the selective expansion or inhibition of specific NK cell subsets.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The amount of NK cells was also found to be remarkedly decreased after 7 day-stimulation with MTB antigens. 42 Our results also showed that MTB lysates impaired the proliferative capacity of NK cells, most likely due to virulence factors released after the destruction of bacterial cells. 52 This effect is reminiscent of a previous study demonstrating that cytomegalovirus infection has the potential to shape the NK cell repertoire, thus resulting in the selective expansion or inhibition of specific NK cell subsets.…”
Section: Discussionsupporting
confidence: 55%
“…[37][38][39] The CD57 + phenotypes of tuberculosis patients in different states of the disease are also divergent. [40][41][42] This may be the reason for the huge heterogeneity in CD57 + phenotype among TB group in our study.…”
Section: Discussionmentioning
confidence: 73%
“…NK cells are essential components of the innate immune response and play a crucial defensive role in the early stages of MTB invasion [ 50 ]. NK cells are primarily derived from bone marrow and can secrete various cytokines, among which interferon-γ (IFN-γ) is one of the most important.…”
Section: Immunological Mechanisms Of Ltbimentioning
confidence: 99%
“…Moreover, there are differences in the phenotypes of NK cells among ATB patients, individuals with LTBI, and healthy controls. Recently, Albayrak et al [ 50 ] classified NK cells found in the blood into three types based on their phenotypes, including CD56 bright , CD56 dim , and CD56 neg NK cells. They found that the ratio of total NK cells and CD56 neg NK cells was lower in individuals with ATB than in those with LTBI.…”
Section: Immunological Mechanisms Of Ltbimentioning
confidence: 99%
“…In recent years, several genome-wide transcriptomic studies have been conducted to identify variations in host gene expression profiles in relation to different states of M. tuberculosis infection [ 10–12 ]. However, while most studies have primarily focused on discerning differences between patients with active TB and individuals with LTBI [ 10 , 13 ], little is known about the diverse host responses among household contacts (HHCs). Thus, the objective of this study was to conduct a prospective investigation in mainland China, aiming to evaluate transcriptome signatures in human peripheral blood mononuclear cells (PBMCs) of HHCs with distinct clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%